2016
DOI: 10.1590/1807-55092016000400913
|View full text |Cite
|
Sign up to set email alerts
|

Promoção da atividade física e da alimentação saudável e a saúde da família em municípios com academia da saúde

Abstract: Rev Bras Educ Fís Esporte, (São Paulo) 2016 Out-Dez; 30(4): 925-36 • 925 Health family, physical activity, and healthy eating IntroductionPromotion of physical activity, healthy eating and family health in municipalities with health gym CDD. 20.ed. 613 . In addition, surveys among samples of adult population in Brazilian capitals have indicated that 60% of adults do not engage in any kind of leisure physical activity and about 85% of people do not practice at least 150 minutes of physical activity in this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
1
13
0
12
Order By: Relevance
“…But, other health professionals also were cited and are important. For example, Florindo et al 10 showed that nutritionists and physical education professionals are very important for promotion healthy food and physical activity in these cities with "Academia da Saúde" 10 . And survey conducted in primary health care settings in Brazil showed that physicians and nurses are important for physical activity promotion 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But, other health professionals also were cited and are important. For example, Florindo et al 10 showed that nutritionists and physical education professionals are very important for promotion healthy food and physical activity in these cities with "Academia da Saúde" 10 . And survey conducted in primary health care settings in Brazil showed that physicians and nurses are important for physical activity promotion 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Details about this selection are describe in other paper 10 . This program was implemented by Brazilian Federal Government in 2011 with objective of contribute for improve physical activity, healthy food and others healthy behaviors in population 11 .…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were found in Santos and Benedetti 5 where they observed Physical Education professionals are the fifth most hired category and present in 49.2% of the teams. It is necessary to highlight the fact that Physical Education professionals are important agents in the qualification of physical activity promotion in the SUS and the family health teams, supported by the NASF 10 . Among the main results in this study, a great part of Physical Education professionals working in NASF, until February 2014, performed individual sessions based mainly in orientation and forwarding to physical activity practice in shared sessions, as well as group sessions, also shared, in gymnastics orientation, walking groups and mixed sessions.…”
Section: Discussionmentioning
confidence: 99%